ANALISIS FAKTOR YANG MEMPENGARUHI KEMANDIRIAN KAB/KOTA DI JAWA TIMUR TAHUN 2021-2024 - Rosydah, Amelia Azza; Faisol, Faisol; Puspita, Erna (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2025)
Regional financial independence is a key indicator of the implementation of regional autonomy, reflecting a region's ability to finance government operations and development without relying on the central government. This study aims to analyze the influence of Local Own-Source Revenue (PAD), the quality of Human Resources (HR), and investment on the level of independence among regencies/municipalities in East Java Province during the 2021-2024 period. The study uses a quantitative approach with panel data regression analysis. The data consists of 152 observations from 38 regencies/municipalities over four years. The independent variables include PAD, the Human Development Index (HDI) as a proxy for HR quality, and Gross Fixed Capital Formation (GFCF) as an indicator of investment. The results show that PAD has a positive and significant effect on regional independence. The quality of human resources also has a positive and significant influence, indicating that improvements in education, health, and living standards enhance a region's capacity to manage development independently Investment likewise contributes positively, though its effect is more moderate compared to the other variables. Simultaneously, all three variables significantly influence regional independence. These findings suggest that increasing PAD, improving human resource quality, and encouraging investment are effective strategies to enhance the ability of local governments to independently manage development and public services on an ongoing basis